THE INFLUENCE OF TAXPAYER'S PERSPECTED BENEFITS, SOCIALIZATION AND INCOME ON TIN OWNERSHIP IN PEMATANG SERAI VILLAGE - Destari Nurlaila Damanik (Institute of Computer Science (IOCS), 2021)
This study examines whether the variable perceived benefits of taxpayers, tax socialization and mandatory income have an effect on the ownership of a Taxpayer Identification Number. Then the data used in this study are primary data derived from questionnaires in which all questionnaires must first be tested for validity and reliability. Then the data obtained were analyzed using multiple regression analysis, normality test, multicollinearity test, heteroscedasticity test, linearity test, partial test (t test), simultaneous test (f test), coefficient of determination analysis. The results of the study state that the variable benefits felt by taxpayers, tax socialization and taxpayer income have a significant effect on the ownership of a Taxpayer Identification Number (TIN).